(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Phayao University has operated the project, 1 faculty 1 model since fiscal year 2012 by assigning the Faculty of Architecture and Department of Science Responsible for Chiang Kham District, Phayao Province. Operating under 3 missions: Research, Academic service to society and the preservation of art and culture by shifting researchers to take responsibility for the project continuously for each fiscal year. Until now 2019, totaling 8 years, the first year that the faculty has adjusted the research model to integrate science. In which 5 disciplines are Architecture, Interior Design, Art and Design, Performing Arts, and Western Music to do a project together with an emphasis on working on the inheritance of Tai Lue wisdom and art and culture in conjunction with the project, together with the academic service project. To develop teachers’ potential and arts and culture preservation projects in promoting student quality to drive the organization of the turbocharged, the operational area is Tai Lue Cultural Village, Yuan Subdistrict, Chiang Kham District, Phayao Province, Thailand. Comparing with Tai Lue cultural villages in a country that is culturally close to the culture is Tai Lue village, Na Yang Tai village, Nam Bak, Luang Prabang Province, Lao PDR by studying the context of the change in arts and culture among the Tai Lue ethnic groups. To analyze for good development practice Integrated Science Research Project on the changing of the world and culture including the development of research administration and develop research groups within the faculties, and to achieve co-operation networks until leading to the exchange of knowledge between researchers and students at the international cooperation level for the purposes. They are (1) to study the relationship between Tai Lue culture in Phayao Province, and Tai Lue, Luang Prabang Province, Laos, in the arts and culture that will lead to the development of design and creation. (2) To manage research projects in the form of integration of science with all disciplines involved. It is expected that there will be a way to produce creative works, designs and/or academic articles from 5 disciplines and international activities.